Design And Development Of A Locking Mechanism For A Gear-Based Prosthetic Knee Joint - Chiang, Xiao Tong (Universiti Sains Malaysia, 2019)
This thesis is based on the project about design and development of a locking mechanism for a gear-based knee joint prosthesis. The purpose to design and develop the locking mechanism is to provide stability when the user is standing upright to avoid sudden buckling or falling down. The project is started with the study of the human gait cycle movement, lower limb prostheses and design of gear-based knee joint prosthesis. Then, this project is followed by conceptual development of locking mechanism, prototype development and testing of the prototype. The final design being selected is an electromagnet based locking mechanism with a control circuit. The electromagnet is controlled by a microcontroller to lock or unlock the knee joint via the position detection by a gyro sensor during thigh movement. During prototype development, the modified gear-based knee joint prosthesis with the proposed locking mechanism are fabricated. Then, an experiment is conducted to test the functionality of the locking mechanism and overall performance of the gear-based knee joint prosthesis. The result shows that the proposed locking mechanism incorporated in the gear-based knee joint is working well with the program loaded to the microcontroller. The electromagnet based locking mechanism also enabled the gear based knee joint to recreate the lower-limb gait cycle closer to that of a healthy individual. Although the measure of the stability performance is not possible due to the unavailability of testing facility, it is obvious that the knee locking mechanism would enhance the stability performance and safety measure of that gear based knee joint prosthesis to some extent. For the development of this project and future works, some suggestions are made for refining the product. The suggestions are to ensure the product is suitable and safe to be used by all the amputees.